An Investigation of The Effect of Low Impact Shock Processes on Breakdown of Sandstone at Meteor Crater - VERMA, ANKIT KUMAR (Trinity College Dublin. School of Natural Sciences. Discipline of Geography, 2019)
Impact cratering is one of the most common geologic processes shaping all the terrestrial planetary bodies and moons in our solar system. The widespread presence of craters on terrestrial planets and moon in the inner solar system shows that impact cratering was a dominant process during the early history of the solar system. Asteroid and comet impacts can influence the geologic and climatic history of terrestrial planets and impact processes can also play a significant role in subsequent rock breakdown on planetary bodies. The formation of impact craters has a catastrophic effect on target lithology, producing a range of heterogeneities and deformation features in rocks. Recognising how these heterogeneities and deformation features affect the mechanisms and kinetics of rock weathering provides a framework for understanding impact inheritance in rock breakdown. Research within the past few decades has revealed extensive shock related features and deformations in rocks in the impact craters. In recent years, stress history and rock control are recognised important in controlling the rate and nature of breakdown. This thesis is the first detailed and comprehensive investigation of the effect of impact metamorphism processes on subsequent rock breakdown. The focus of this thesis is to understand how the inheritance from low impact shock (<10 GPa) deformations and heterogeneities affects subsequent rock breakdown. This is achieved through a combined field and laboratory approaches that examined rock breakdown on impacted, and non-impacted rocks of the same lithology that are exposed at Meteor Crater site, Arizona. Rock hardness data and topographic data using a Structure from Motion (SfM) photogrammetry-based method developed in this thesis was used to compare rock breakdown between impacted and non-impacted sandstone outcrops at Meteor Crater site. The topographic data collected in the field was analysed using a range of roughness and morphometric parameters. The rock samples collected from the Meteor Crater and additional small number of impactite samples from West Clearwater Impact Structure (Canada) and Ries Crater (Germany) were characterised and assigned a shock level in the laboratory using different analytical techniques (petrographic microscopy, powder X-ray diffraction, scanning electron microscopy, X-ray computed tomography). Further, these samples were used in a physical weathering simulation in semi-arid conditions. The rock samples were analysed before and after the experiments to identify and quantify changes. This research advanced the field of rock breakdown by providing insight into the influence of impact processes on subsequent rock breakdown processes. This thesis has revealed the following new insights: (1) The low impact shocked sedimentary rocks show a decrease in porosity. (2) Macrofracturing and microfracturing caused by low impact shock occur in all types of impactites. Macrofracturs of 0.1-0.2 mm and microfractures 0.1-5 µm in aperture are observed in all types of impactites. (3) The rock breakdown experiment results showed that impactites exhibit an accelerated decline in strength compared to non-impacted control samples. (4) Rock type and impact deformation history are important in controlling the rate of deterioration. (5) Close-range Structure from Motion (SfM) photogrammetry can be used to collect sub-mm resolution topographic data on rock surfaces in the field. (6) Rock hardness, rock surface roughness and morphometric analysis revealed no substantial difference in terms of nature of breakdown between low shocked and ushocked Moenkopi Sandstone at Meteor Crater site. (7) Aspect related microclimate within Meteor Crater affects the nature of rock breakdown on different crater sidewalls. This thesis has improved the understanding of low shock deformed sandstones in impact craters and provided an insight into the role of low shock inheritance on subsequent rock breakdown. This research also advances the data collection methods on rock breakdown in field and laboratory settings by developing and applying novel SfM photogrammetry and X-ray computed tomography (CT) techniques.
APPROVED
Keywords: Rock breakdown; Impact cratering; Impact metamorphism; Impactites; Impact inheritence; Breakdown of impactites; Meteor Crater; Rock weathering